PENGETAHUAN INVESTASI, MOTIVASI INVESTASI, LITERASI KEUANGAN DAN PERSEPSI RESIKO PENGARUHNYA TERHADAP MINAT INVESTASI PADA PASAR MODAL - Hikmah, Hikmah; Rustam, Triana Ananda (SULTANIST: Jurnal Manajemen dan Keuangan, 2020)
Â At the present time there are many financial effects that exist both in the money market and in the capital market. This study aims to determine investment knowledge, investment motivation, financial literacy and risk perceptions of their impact on public investment interest in the capital market in Batam City. The population in this study were 2 sub-districts in Batam City, namely Batu Aji District and Sagulung District. The sample in this study was 204 respondents. The prescription in this research is people who are interested in investing in the capital market. The sampling technique used was purposive sampling. The analysis method used is SEM with the SmartPLS application. The results showed that investment knowledge has a positive and significant effect on investment interest, investment motivation has a positive and significant effect on investment interest, financial literacy has a positive and significant effect on investment interest, risk perception has a positive and significant effect on investment interest in the city of Batam